2013
DOI: 10.1016/j.neuron.2013.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction and Vision Meet in the Retina

Abstract: In fish, axons that originate in the olfactory bulb innervate the retina and increase luminance sensitivity. In this issue of Neuron, Esposti et al. (2013) investigate the mechanisms underlying this interaction to report modulation of synaptic gain and sensitivity in OFF bipolar cells but rarely in ON bipolar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…Studies applying multivariate analysis techniques have also found evidence that the HC contains activation patterns that are sensitive to scene‐related information [Bonnici et al, 2012; Liang et al, 2013; but see Diana et al, 2008]. Overall, these extant data, when viewed alongside the large‐scale analysis of individual‐level data reported here, suggest that the HC should be considered a key region in the putative scene processing network [see also Kornblith et al, 2013; Kreiman et al, 2000]. While these results implicate HC in the online processing of visual scenes—contrary to the perspective that HC activation is primarily driven by internally generated thought [Buckner et al, 2008]—it is not possible in this block design study to determine whether HC response is being driven by perceptual processing or scene maintenance across trials [Zeidman et al, 2015].…”
Section: Discussionmentioning
confidence: 51%
“…Studies applying multivariate analysis techniques have also found evidence that the HC contains activation patterns that are sensitive to scene‐related information [Bonnici et al, 2012; Liang et al, 2013; but see Diana et al, 2008]. Overall, these extant data, when viewed alongside the large‐scale analysis of individual‐level data reported here, suggest that the HC should be considered a key region in the putative scene processing network [see also Kornblith et al, 2013; Kreiman et al, 2000]. While these results implicate HC in the online processing of visual scenes—contrary to the perspective that HC activation is primarily driven by internally generated thought [Buckner et al, 2008]—it is not possible in this block design study to determine whether HC response is being driven by perceptual processing or scene maintenance across trials [Zeidman et al, 2015].…”
Section: Discussionmentioning
confidence: 51%
“…Taking a mechanistic approach might provide researchers with a way to quantitatively compare the effects of all predation cues across different sensory systems (visual versus chemical versus mechanical) and, more importantly, could demonstrate how prey integrate the different sensory inputs. A recent study demonstrated that, in zebrafish, axons originating from the olfactory bulb innervate the retina and increase luminance sensitivity, suggesting that the interaction between these two sensory systems might influence reproductive behaviour by increasing sensitivity to visual courtship coloration in potential mates (Dowling, 2013;Esposti et al, 2013). It is not hard to imagine that such interactions between sensory systems would be adaptive upon the detection by prey of visual and chemical cues from predators.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a surprisingly high variation in the effect of ocean acidification among closely related species , indicating that recognising the GABA A involvement is only the first step towards understanding the complex effect of such stressors on prey risk assessment. There is an abundance of information on the structure and function of the olfactory system (Derby and Sorensen, 2008;Dowling, 2013;Firestein, 2001;Hamdani and Døving, 2003;Li, 2014) and the neuroendocrine system of aquatic organisms (Dennis et al, 2014;Døving and Lastein, 2009;Dufty et al, 2002). In addition, much is known about the way predator odours are processed in terrestrial animals (Hegab and Wei, 2014;Li, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, glypicans have been shown to play a role in axon guidance [310, 324], and in the formation of excitatory synapses [325, 326]. …”
Section: The Role Of Glypicans In Breast Cancer Progressionmentioning
confidence: 99%